Co‐ and Post‐Translational Protein Folding in the ER. (22nd April 2016) - Ellgaard, Lars; McCaul, Nicholas; Chatsisvili, Anna; Braakman, Ineke
Abstract : The endoplasmic reticulum (ER) produces a plethora of membrane and secretory proteins, which must fold and assemble correctly before ER exit – if these processes fail, misfolded species accumulate in the ER or are degraded. Here, we review chaperone‐assisted co‐ and post‐translational folding and assembly in the ER and the influence of protein modifications, emphasizing how method development has advanced the field by allowing folding studies inside living cells. The laboratory of Dr Ari Helenius pioneered many of these studies with the influenza virus hemagglutinin (HA) protein, which is a trimer. This cartoon of an HA monomer drawn by Dr Ari Helenius shows the receptor domain (R), the esterase‐like domain (E′) and the stem domain (S). Native HA has six disulfide bonds (orange lines). A, B, E, F1 and F2 indicate the positions of antigenic epitopes. Abstract : The biophysical rules that govern folding of small, single‐domain proteins in dilute solutions are now quite well understood. The mechanisms underlying co‐translational folding of multidomain and membrane‐spanning proteins in complex cellular environments are often less clear. The endoplasmic reticulum (ER) produces a plethora of membrane and secretory proteins, which must fold and assemble correctly before ER exit – if these processes fail, misfolded species accumulate in the ER or are degraded. The ER differs from other cellular organelles in terms of the physicochemical environment and the variety of ER‐specific protein modifications. Here, we review chaperone‐assisted co‐ and post‐translational folding and assembly in the ER and underline the influence of protein modifications on these processes. We emphasize how method development has helped advance the field by allowing researchers to monitor the progression of folding as it occurs inside living cells, while at the same time probing the intricate relationship between protein modifications during folding.